Shear Strength of Compacted Clays as Affected by Mineral Content and Wet-Dry Cycles - Frederick Nai Charkley; Kunyong Zhang; Guoxiong Mei (Advances in Civil Engineering)
The behaviors of high-plasticity clays depend largely on the clay mineral content. Recently, it has been observed that sudden slope failures of most clay slopes occur in regions pronounced with repeated rainfall and sunny climate. The reason for this is still unclear. Examining the effect of clay minerals and drastic weather changes on shear strength will be useful in predicting the performance of structures built in such soils and to take precautionary measures to improve the properties before failure. Therefore, a series of quick direct shearing tests were conducted on 11 artificial clay mixtures. The cohesion and frictional strength properties were determined and linked to the proportion of clay minerals and the number of wetting and drying cycles. The results show a significant reduction in shear strength after exposure to wetting and drying. Generally, montmorillonite-dominated mixtures were less susceptible to the changes in cohesion strength than kaolin-dominated mixtures, and the reduction in frictional strength was relatively insignificant.